Neurotrophins stimulate phosphorylation of synapsin I by MAP kinase and regulate synapsin I-actin interactions. - Jovanovic, J N (1996)
The ability of neurotrophins to modulate the survival and differentiation of neuronal populations involves the Trk/MAP (mitogen-activated protein kinase) kinase signaling pathway. More recently, neurotrophins have also been shown to regulate synaptic transmission. The synapsins are a family of neuron-specific phosphoproteins that play a role in regulation of neurotransmitter release, in axonal elongation, and in formation and maintenance of synaptic contacts. We report here that synapsin I is a downstream effector for the neurotrophin/Trk/MAP kinase cascade. Using purified components, we show that MAP kinase stoichiometrically phosphorylated synapsin I at three sites (Ser-62, Ser-67, and Ser-549). Phosphorylation of these sites was detected in rat brain homogenates, in cultured cerebrocortical neurons, and in isolated presynaptic terminals. Brain-derived neurotrophic factor and nerve growth factor upregulated phosphorylation of synapsin I at MAP kinase-dependent sites in intact cerebrocortical neurons and PC12 cells, respectively, while KCl- induced depolarization of cultured neurons decreased the phosphorylation state at these sites. MAP kinase-dependent phosphorylation of synapsin I significantly reduced its ability to promote G-actin polymerization and to bundle actin filaments. The results suggest that MAP kinase-dependent phosphorylation of synapsin I may contribute to the modulation of synaptic plasticity by neurotrophins and by other signaling pathways that converge at the level of MAP kinase activation.